Alien resurrection - Jeunet, Jean-Pierre, 1955-; Carroll, Gordon, 1928-2005.; Whedon, Joss, 1964-; Weaver, Sigourney, 1949-; Ryder, Winona, 1971-; Perlman, Ron, 1950-; Hedaya, Dan.; Freeman, J. E.; Bourif, Brad.; Wincott, Michael, 1959-; Khondji, Darius; Schneid, Hervé.; et al. (Beverly Hills, Calif. : Twentieth Century Fox Home Entertainment, 1999)
Two hundred years have passed since Ripley made the ultimate sacrifice on Fiorina 161. But over the years, and after seven horrific failures, scientists have finally cloned a perfect replica of Ripley, which includes the alien Queen growing inside her at the time of her death. But this new breed of alien is far more intelligent than its predecessors, a fact the scientists don't realize until after The Betty has arrived with additional human hosts.
Title from packaging.
Contains the original 1997 theatrical version and the all-new 2003 special edition with an alternate opening and ending.
Director of photography, Darius Khondji ; editor, Herve Schneid ; music, John Frizell.
Sigourney Weaver, Winona Ryder, Ron Perlman, Dan Hedaya, J.E. Freeman, Brad Dourif, Michael Wincott.
Rated R.
DVD, widescreen presentation.
Keywords: Life on other planets -- Drama; Human-alien encounters -- Drama; Vida en otros planetas -- Teatro; Science fiction films; Feature films; Video recordings for the hearing impaired